Mass Change of Ruthenium Oxide During Methanol Oxidation - Bae, Sang-Eun; Yoon, Jung-Hyun; Lee, Chi-Woo (Asian Journal of Chemistry, 2013)
An electrochemical quartz crystal microbalance was employed to investigate the electrochemical dynamics of a ruthenium oxide (RuOx) film in aqueous solutions. The ruthenium oxide film was prepared by electrochemical deposition, where 5 H2O molecules per Ru were incorporated into the film. During the potential cycles of the ruthenium oxide film in an electrolyte, a proton ion is deserted and inserted repeatedly, where two water molecules are always accompanied. The prepared ruthenium oxide film exhibits electrocatalytic activity toward the oxidation reaction of methanol. During the electrocatalytic reaction, the mass of the ruthenium oxide increases slightly, indicating that there are adsorptions of some intermediates on the ruthenium oxide film produced in the oxidation reaction of methanol.